Potential influence of p16 immunohistochemical staining on the diagnosis of squamous cell lesions in cervical biopsy specimens: observation from cytologic‐histologic correlation. Issue 12 (11th October 2018) - Yang, Jack; Elliott, Alexis; Hoffa, Anne L.; Herring, Nicole; Houser, Patricia M.
Abstract : Background: The p16 immunohistochemical (IHC) marker has been used increasingly as an adjunct to morphologic assessment of cervical biopsies in which the differential diagnoses include high‐grade squamous intraepithelial lesion (HSIL) and its mimics. The objective of this study was to assess the potential influence of p16 IHC staining on the evaluation of cervical biopsy as observed through cytologic‐histologic correlation (CHC). Methods: Cervical biopsy samples that had cytologic diagnoses of either low‐grade squamous intraepithelial lesion (LSIL) or HSIL and also had histologic follow‐up were retrieved from the department database. CHC and the use of p16 IHC from 2 periods (group 1, 2008; group 2, 2014‐2016) were compared and analyzed. Results: Histology on 452 samples from patients who had prior LSIL cytology in group 1 yielded 126 benign (27.9%), 272 LSIL (60.2%), and 54 HSIL (11.9%) diagnoses. By comparison, 491 samples from the patients in group 2 yielded 106 benign (21.6%), 277 LSIL (56.4%), and 108 HSIL (22.0%) diagnoses. The difference in CHC discrepancies between the 2 groups was significant ( P = .0001), mainly because of the increased diagnosis of HSIL in group 2. Although p16 IHC was not applied to any sample from group 1, it was performed on 141 of 491 samples (28.7%) from group 2. Further follow‐up of patients who had histologic HSIL revealed that residual HSIL was identified significantly more often in those who did not have p16 IHC applied in the preceding cervical biopsy than in those did ( P = .0004). A similar comparison was performed between 113 patients from group 1 and 152 patients from group 2 who had a prior diagnosis of HSIL cytology, and the difference was statistically insignificant. Conclusions: The use of p16 IHC on cervical biopsies in patients who had a prior cytologic diagnosis of LSIL may lead to greater detection and upgrading of HSIL, thereby compounding the discrepancy in CHC. Abstract : The potential influence of p16 immunohistochemical staining on the assessment of cervical biopsies is evaluated using results from cytologic‐histologic correlation. The findings indicate that, on cervical biopsy specimens with a previous cytologic diagnosis of low‐grade squamous intraepithelial lesion, p16 immunohistochemistry may lead to an increase in the detection and upgrading of high‐grade squamous intraepithelial lesion.